2021
DOI: 10.1152/ajprenal.00154.2021
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of lisinopril and empagliflozin in a mouse model of hypertension-accelerated diabetic kidney disease

Abstract: Hypertension is a critical comorbidity for progression of diabetic kidney disease (DKD). To facilitate development of novel therapeutic interventions with the potential to control disease progression, there is a need to establish translational animal models that predict treatment effects in human DKD. The present study aimed to characterize renal disease and outcomes of standard of medical care in a mouse model of advanced DKD facilitated by adeno-associated virus (AAV)-mediated renin overexpression in unineph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…RAAS regulates blood pressure, salt balance, and fluid homeostasis [ 32 ], and RAAS blockade with ACE inhibitors (ACEI) or angiotensin receptor blockers (ARB) is often used to modify hyperfiltration states and delay progression of renal disease [ 33 ]. Drugs that control hypertension (lisinopril) and hyperglycemia (empagliflozin) were also shown to improve the physiological and histopathological features of kidney disease in a mouse model of hypertension-accelerated progressive DKD [ 34 ]. Moreover, treatment with N-acetyl-seryl-aspartyl-proline (Ac-SDKP), a naturally occurring immunomodulatory and angiogenic peptide mainly produced through enzymatic hydrolysis involving meprin-α and prolyl oligopeptidase, has been shown to partially improve end-organ damage by reducing inflammation and fibrosis, and promoting angiogenesis [ 35 ].…”
Section: Influence Of Hyperglycemia On Diabetes-mediated Cellular Alterationsmentioning
confidence: 99%
“…RAAS regulates blood pressure, salt balance, and fluid homeostasis [ 32 ], and RAAS blockade with ACE inhibitors (ACEI) or angiotensin receptor blockers (ARB) is often used to modify hyperfiltration states and delay progression of renal disease [ 33 ]. Drugs that control hypertension (lisinopril) and hyperglycemia (empagliflozin) were also shown to improve the physiological and histopathological features of kidney disease in a mouse model of hypertension-accelerated progressive DKD [ 34 ]. Moreover, treatment with N-acetyl-seryl-aspartyl-proline (Ac-SDKP), a naturally occurring immunomodulatory and angiogenic peptide mainly produced through enzymatic hydrolysis involving meprin-α and prolyl oligopeptidase, has been shown to partially improve end-organ damage by reducing inflammation and fibrosis, and promoting angiogenesis [ 35 ].…”
Section: Influence Of Hyperglycemia On Diabetes-mediated Cellular Alterationsmentioning
confidence: 99%
“…Typically, tissue segmentation tasks are demanding in heterogeneous sample sets (like kidney biopsies) and therefore traditional bottlenecks in image analysis workflows. DL has great potential to accelerate segmentation tasks and has already been applied to classify glomerulosclerosis 27 or immunofluorescence‐based glomerular morphometry. 14 We custom‐trained two DL networks for the virtual microdissection of glomeruli, all cells by DAPI‐fluorescence, and podocytes using nuclear IF‐markers.…”
Section: Discussionmentioning
confidence: 99%
“…The UNx-Renin mouse represents a promising model of progressive DKD ( Harlan et al, 2018b ). Accordingly, ReninAAV administration induces persistent hypertension and has recently been shown to accelerate DKD progression in diabetic UNx mice ( Harlan et al, 2018b ; Østergaard et al, 2021 ). Our study corroborates previous findings in the UNx-Renin model, demonstrating biochemical and histological features of progressive DKD, notably severe albuminuria and advanced glomerulosclerosis ( Harlan et al, 2018a ; 2018b ; Østergaard et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, ReninAAV administration induces persistent hypertension and has recently been shown to accelerate DKD progression in diabetic UNx mice ( Harlan et al, 2018b ; Østergaard et al, 2021 ). Our study corroborates previous findings in the UNx-Renin model, demonstrating biochemical and histological features of progressive DKD, notably severe albuminuria and advanced glomerulosclerosis ( Harlan et al, 2018a ; 2018b ; Østergaard et al, 2021 ). Although several transcriptomic studies have been reported in the db/db UNx and UNx-Renin mouse models, knowledge on disease-associated gene expression changes in these models is based on preselected gene sets ( Ninichuk et al, 2007 ; Harlan et al, 2018a , b ).…”
Section: Discussionmentioning
confidence: 99%